Implementation of e-OPEN Application as a Strategic Innovation of Public Services in the Pandemic COVID-19 Era in Bekasi - Rahayu, Susi Dian; Rofieq, Ainur; Aini, Nurul (The Sunan Ampel Review of Political and Social Sciences, 2023)
The COVID-19 pandemic that has hit almost the entire world, including Indonesia, has affected all aspects of life, one of which is public services. The government has issued a policy for the whole community so that every activity is carried out online or online to prevent the spread of COVID-19 cases. All parties, especially the government, must innovate to encourage more effective and efficient public services by keeping up with the times and advancing technology. This prompted the Bekasi City Disdukcapil to create an application-based innovation called e-OPEN. This study discusses how to implement the implementation of e-Open in population services in Bekasi City. The method used in this research is the descriptive qualitative method. Data collection is done by observation and literature study. Based on the research results, the e-Open application belonging to the Bekasi City Disdukcapil is considered quite effective and easily accepted by the public. This application allows busy people to manage and access their population data anytime and anywhere easily. Through the Halo Pamor menu, people with limitations in using the application also feel helped by the presence of the prestige task force.